Effect of different targeted calyxes on the treatment of multi-site calculi in the postural drainage lithotripsy system - Yang, Tao; Wu, Chong; Dai, Liangliang; Hu, Zhixiong; Song, Rijin; Meng, Xianghu; Shi, Honglei (Frontiers in Medicine, 2023)
Objectives We developed a postural drainage lithotripsy system (PDLS) that can provide an individualized inversion and overturning angle and uses gravity to remove residual fragments (RFs). This study aimed to evaluate the effect of different targeted calyces on treating multi-site stones in PDLS. Methods A total of 20 stones with different sizes and diameters of 0–4 mm were placed in the kidney model through ureteroscopy, and 20 stones were evenly scattered in the middle calyx and the lower calyx of the model. The ventral-middle calyx, the dorsal-middle calyx, the ventral-lower calyx, and the dorsal-lower calyx were used as the targeted calyx of PDLS to treat multi-site stones. During treatment, if the stone moved from the starting position of the renal calyx to the ureteropelvic junction, it was recorded as “passing through.” The clearance rate was recorded, and the efficacy of different targeted calyxes in the treatment of multiple-site calyx was compared. Each model was treated with four different targeted calyxes, and 20 models were tested 80 times. Results When the lower calyx was the targeted calyx, the total stone clearance rate was higher than when the middle calyx was the locating calyx (94.5 vs. 64%, P = 0.000), and the result was statistically significant. Conclusions Choosing the lower calyx as the targeted calyx, we can obtain a better stone clearance rate. However, there is no significant difference between the ventral lower calyx and the dorsal lower calyx.